The Role of the Headmaster in Establishing Exemplary Schools - Indri Indri (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research analyzes the character of the madrasah principal in leading educational institutions. The objective of this study is to elucidate the significance of a madrasah head's virtuous character as a leader, which undoubtedly influences the persons and institutions under their guidance. This study is a qualitative case investigation conducted at a Madrasah located in Kartasura during the year 2022. Employing the interview technique with the headmaster, two educators, two parental figures of students, and observation. Triangulation is employed to verify the accuracy of the data by juxtaposing it with interviews and observations. This study employed interactive analysis. The findings of this investigation: The head of Madrasah embodies the qualities of uswatun hasanah, which include adherence to instructions, democratic leadership, and recognising teachers as individuals with their own capabilities. They possess excellent listening and speaking skills, empathy towards others, and the ability to make sound judgements. The term used to refer to this character is "nguwongke". Recommendations in this study propose that leaders of educational institutions should strive to establish efficient two-way communication by minimising mutual blame and adopting an attitude of mutual evaluation. Additionally, it is advised that leaders raise awareness among all stakeholders of educational institutions regarding the importance of frequently recognising and rewarding staff and subordinates. The character embodying the principles of the madrasah is characterised by democratic objectivity, serving as a role model, doing what they preach, making intelligent decisions, being attentive to others, and possessing effective communication skills. This character possesses the capability to cultivate self-leadership.